Introduction to robotics mechanics and control - Craig, John J. (Pearson, 2018)
The 4th Edition features a balance of application and theory, introducing the science and engineering of mechanical manipulation--establishing and building on foundational understanding of mechanics, control theory, and computer science. With an emphasis on computational aspects of problems, the text aims to present material in a simple, intuitive way.